2011
DOI: 10.1007/s12013-011-9190-8
|View full text |Cite
|
Sign up to set email alerts
|

Modified Low Density Lipoproteins Decrease the Activity and Expression of Lysosomal Acid Lipase in Human Endothelial and Smooth Muscle Cells

Abstract: Lysosomal acid lipase (LAL), the only lysosomal enzyme involved in the hydrolysis of LDL-cholesteryl esters, is a key regulator of cellular cholesterol and fatty acid homeostasis and its deficiency contributes to the pathophysiology of various diseases. In this study, we questioned whether oxidized or glycated LDL, a common occurrence in atherosclerosis and diabetes, affect the activity and expression of LAL in vascular endothelial cells (EC) and smooth muscle cells (SMC). LAL activity and expression were assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…36 37 38 OXLAMs, particularly the isomers and enantiomers produced by free radical mediated oxidation,35 39 68 have been mechanistically linked to cardiovascular disease pathogenesis. Mechanisms include inducing the formation of macrophage foam cells41 42; endothelial cell activation43; migration, proliferation, and foam cell formation of vascular smooth muscle cells44 69; and inhibition of lysosomal hydrolysis of low density lipoprotein cholesteryl esters70 (fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 37 38 OXLAMs, particularly the isomers and enantiomers produced by free radical mediated oxidation,35 39 68 have been mechanistically linked to cardiovascular disease pathogenesis. Mechanisms include inducing the formation of macrophage foam cells41 42; endothelial cell activation43; migration, proliferation, and foam cell formation of vascular smooth muscle cells44 69; and inhibition of lysosomal hydrolysis of low density lipoprotein cholesteryl esters70 (fig 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated by Heltianu et al ( 2011 ) that in some cell types LIPA expression increases with liver-X-receptor (LXR) and peroxisome proliferator-activated receptor (PPAR) agonists. LIPA is not known to contain an LXR or PPAR response element in its promoter region.…”
Section: Lysosomal Acid Lipasementioning
confidence: 85%
“…Translocation of TFEB to the nucleus and a modest (0.2-fold) upregulation of LIPA also occurred after a 12 h incubation of peritoneal macrophages with oxidized LDL (oxLDL); the TFEB nuclear localization was reduced at 24 h of oxLDL incubation, however, indicating this response of LIPA is likely mild and transient (Emanuel et al, 2014 ). Heltianu et al ( 2011 ) reported no change in LIPA expression in SMCs and a 20% reduction in LIPA expression in endothelial cells incubated with oxLDL for 24 h. Further studies are required to confirm the importance and cell specificity of TFEB-dependent upregulation of LIPA in response to modified forms of LDL and cellular stress induced by excess cell cholesterol.…”
Section: Lysosomal Acid Lipasementioning
confidence: 97%
“…Oxidized LDL can then bind and inactivate cathepsins with high affinity 30 , inactivate other proteases including the NaβGases 31 , and produce a form of apolipoproteinB that is highly resistant to hydrolysis 32, 33 . OxLDL has also been demonstrated in endothelial and smooth muscle cells to inhibit activity and expression of the enzyme crucial to cholesterol ester hydrolysis, lysosomal acid lipase 34 . Most recently, the formation of cholesterol micro-crystals and ensuing disruption of lysosomal integrity has directly been linked to the build-up of oxLDL in the lysosomal compartment 14 .…”
Section: Discussionmentioning
confidence: 99%